2020
DOI: 10.1097/htr.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tau in Military Personnel Relates to Chronic Symptoms Following Traumatic Brain Injury

Abstract: Objective: To understand the relationships between traumatic brain injury (TBI), blood biomarkers, and symptoms of posttraumatic stress disorder (PTSD), depression, and postconcussive syndrome symptoms (PCS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“… 7 , 25 , 28 Indeed, our laboratory has previously observed that plasma Nf-L concentrations were elevated in military personnel who had sustained repetitive TBIs compared with those with 1 or 2 TBIs, but no differences were observed between control and TBI groups. 29 Despite recent progress in SRCs, the prognostic value of Nf-L is yet to be fully ascertained. We hypothesize that Nf-L has limited sensitivity in milder cases of SRC and may become more evident as the number of SRCs sustained increases.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 25 , 28 Indeed, our laboratory has previously observed that plasma Nf-L concentrations were elevated in military personnel who had sustained repetitive TBIs compared with those with 1 or 2 TBIs, but no differences were observed between control and TBI groups. 29 Despite recent progress in SRCs, the prognostic value of Nf-L is yet to be fully ascertained. We hypothesize that Nf-L has limited sensitivity in milder cases of SRC and may become more evident as the number of SRCs sustained increases.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker studies in TBI have focused on plasma and serum levels of proteins found in brain cells such as tau, p-tau, and neurofilament light chain (NfL) ( 152 , 153 ); glial fibrillary acidic protein (GFAP), that is released from astrocytes ( 13 ); and ubiquitin carboxyl-terminal hydrolase isozyme L1 (UCHL1), a brain-specific deubiquitinating enzyme ( 154 ). NfL, GFAP, tau and UCHL1 have been linked to TBI severity, poor recovery, as well as PCS and PTSD symptomology in a variety of populations, including civilians ( 23 , 155 , 156 ), athletes ( 157 , 158 ) and military personnel ( 11 , 90 , 159 ). Other studies have evaluated levels of inflammatory markers ( 134 137 ) as previously discussed in this article.…”
Section: Extracellular Vesicles In Tbimentioning
confidence: 99%
“…Lifestyle, sex, genetic, and social factors, medical history, including previous head injuries, are all likely important determinants in TBI recovery (7,9). Indeed, sustaining multiple TBIs has been linked to lasting or worsening neurobehavioral symptoms, placing populations such as service members and contactsport athletes at a higher risk for worse outcomes following a TBI (10)(11)(12). The heterogeneous nature of TBI and limited understanding of underlying pathology represents a challenge to the development of effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Blood biomarkers have been investigated as predictors of neuroimaging abnormalities (abnormal CT and MRI scans) (9,20,(35)(36)(37)(38). Blood biomarkers have uncertain value in predicting the late effects of TBI (39)(40)(41)(42), in detecting sub-concussive blows to the head (43)(44)(45)(46), and in predicting readiness for return to play (47). Questions remain as to the preferred time to measure blood biomarkers, the preferred and Tmax are mid-range estimates † S100B is eliminated by first order kinetics.…”
Section: Introductionmentioning
confidence: 99%